2019
DOI: 10.1039/c8fo02460j
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene ameliorates systemic inflammation-induced synaptic dysfunction via improving insulin resistance and mitochondrial dysfunction in the liver–brain axis

Abstract: Lycopene supplementation effectively attenuated systemic inflammation-induced synaptic dysfunction through ameliorating insulin resistance, mitochondrial dysfunction and inflammatory response in the mouse liver–brain axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 57 publications
2
21
0
1
Order By: Relevance
“…[54] LPS-induced neuroinflammation was reported to cause cognitive impairment and nervous-system damage in mice. [55] Interestingly, the mRNA expression fluctuations of Bdnf and inflammatory cytokines showed almost opposite trends under HFD, which suggests that inflammatory cytokines could represent a major factor related to the decrease of Bdnf levels. Furthermore, HFD induces inflammation in the central nervous system, which further leads to cognitive impairments and decreases the expression of PSD-95 and BDNF.…”
Section: Discussionmentioning
confidence: 98%
“…[54] LPS-induced neuroinflammation was reported to cause cognitive impairment and nervous-system damage in mice. [55] Interestingly, the mRNA expression fluctuations of Bdnf and inflammatory cytokines showed almost opposite trends under HFD, which suggests that inflammatory cytokines could represent a major factor related to the decrease of Bdnf levels. Furthermore, HFD induces inflammation in the central nervous system, which further leads to cognitive impairments and decreases the expression of PSD-95 and BDNF.…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, a number of NRF2-activating compounds have shown beneficial effects in MS model systems. NRF2 activation by resveratrol, lycopene, quercetin, and ferulic acid has been shown to reduce LPS-induced neurotoxicity, improve synaptic and mitochondrial function, and reduce inflammatory markers as well as gliosis (Chen et al., 2017; Khan et al., 2018; Rehman et al., 2019; Wang et al., 2019). In the EAE model, DMF treatment increased NRF2 activation in neurons and glial cells and improved disease score ratings, an effect that was lost with NRF2 deletion (Linker et al., 2011).…”
Section: Nrf2 and Msmentioning
confidence: 99%
“…In the initial study, a decreased number of mitochondria have been found in insulin-resistant skeletal muscle cells, suggesting that mitochondrial function is impaired in insulin-resistant skeletal muscle cells (Perreault et al, 2018). As research progresses, hepatic fatty acid–induced mitochondrial dysfunction has also been proved to play an important role in the development of hepatic insulin resistance (Wang et al, 2017b; Wang et al, 2018; Wang et al, 2019b). Recently, it has been widely recognized that mitochondrial autophagy (mitophagy), a catabolic process, can selectively remove damaged mitochondria by autophagolysosomes to maintain mitochondrial function and energy metabolism (Redmann et al, 2018; Li et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%